2009
DOI: 10.1007/s00595-008-3863-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection of sporadic synchronous gastric and jejunal gastrointestinal stromal tumors: Report of a case

Abstract: Multicentricity of gastrointestinal stromal tumors (GISTs) has been described only in patients with neurofibromatosis type 1 (NF1) or within the small intestine, and different pathogenetic mechanisms are involved. We report a case of synchronous sporadic gastric and jejunal GISTs, which were resected laparoscopically in a 67-year-old man. Immunohistochemical analysis revealed that both lesions were KIT (CD117)-positive, but that the gastric lesion was CD34-positive, whereas the jejunal one was Vimentin-, S-100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
(114 reference statements)
1
9
0
Order By: Relevance
“…DeMatteo et al [16] suggested that complete gross resection of the tumor without lymphadenectomy is sufficient surgical treatment for GISTs, as the status of the microscopic margin of resection does not affect survival and lymph node metastasis is rare. Today, wedge resection is widely accepted as the treatment of choice for most gastric GISTs, and several recent studies support the feasibility of laparoscopic wedge or partial resection of gastric GISTs [17][18][19][20][21]. The National Comprehensive Cancer Network taskforce report suggests that the laparoscopic approach can be applied to tumors larger than 5 cm, depending on their location and shape [22], so many investigators have adopted the technique successfully for larger tumors [17].…”
Section: Discussionmentioning
confidence: 97%
“…DeMatteo et al [16] suggested that complete gross resection of the tumor without lymphadenectomy is sufficient surgical treatment for GISTs, as the status of the microscopic margin of resection does not affect survival and lymph node metastasis is rare. Today, wedge resection is widely accepted as the treatment of choice for most gastric GISTs, and several recent studies support the feasibility of laparoscopic wedge or partial resection of gastric GISTs [17][18][19][20][21]. The National Comprehensive Cancer Network taskforce report suggests that the laparoscopic approach can be applied to tumors larger than 5 cm, depending on their location and shape [22], so many investigators have adopted the technique successfully for larger tumors [17].…”
Section: Discussionmentioning
confidence: 97%
“…This assumption is supported by some case reports. One case of esophageal cancer with sigmoid colon cancer treated by laparoscopic surgery and another case of laparoscopic resection of sporadic synchronous gastric and jejunal gastrointestinal stromal tumors have been reported [18,19]. In addition, several cases of simultaneous laparoscopy-assisted resection for synchronous rectal and gastric cancer have been reported, and the results revealed a fast recovery, low incidence of complication and a good cosmetic result [20e22].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] We proposed a standardized system of operation selection based on tumor size, location, and growth morphology for suspected gastric GISTs. Between February 1994 and April 2009, 45 patients underwent laparoscopic resection of suspected gastric GISTs at Iwate Medical University Hospital.…”
Section: Discussionmentioning
confidence: 99%